The Influence of Compensation, PO-Fit and Islamic Work Ethics on Employee Performance at BSI KCP Palembang KM 6 - Farizki, Muhammad; Hildayanti, Siti Komariah; Emilda, Emilda (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to analyze and determine the effect of compensation, PO-fit and Islamic wotk ethics partially and simultaneously on employee performance at BSI KCP Palembang KM 6. This study used quantitative analysis methods. The sampling technique uses saturated sampling where all 52 employees are respondents. The data in this study was obtained through the distribution of questionnaires to all employees of BSI KCP Palembang KM 6. Analysis techniques The data analysis technique uses SPSS software version 24, which consists of validity and reliability tests, classical assumption tests, hypothesis tests and multiple regression analysis. Based on the results of the t test, Compensation, PO-Fit and Islamic Work Ethics partially have a positive and significant effect on employee performance by obtaining a sig value of 0.000 < 0.05. Based on the results of the F test, compensation, PO-Fit and Islamic Work Ethics simultaneously affect the job satisfaction of BSI KCP Palembang KM 6 employees with a sig value of 0.00 < 0.05. The Correlation Coefficient (R) with a value of 0.959 shows the relationship (correlation) between compensation variables, PO-fit and Islamic work ethics on employee performance. The Coefficient of Determination (R2) of 92% is influenced by compensation, PO-fit and Islamic work ethics while the remaining 8% is influenced by other variables